2020
DOI: 10.1111/all.14646
|View full text |Cite
|
Sign up to set email alerts
|

Spotlight on microRNAs in allergy and asthma

Abstract: This is an open access article under the terms of the Creative Commons Attribution-NonCommercial License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited and is not used for commercial purposes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
63
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 108 publications
(79 citation statements)
references
References 200 publications
(360 reference statements)
3
63
0
1
Order By: Relevance
“…The profiling results and the outline of the study are briefly presented in the Additional file 1 . From the miRNAs whose expression significantly differed in asthmatics and controls in the profiling study, we chose those that had been previously tested in serum and were related to the presence of asthma or its clinical features [ 15 , 20 ]. Additionally, although not shown as significant in the profiling results, miRNA-126a-5p was also included in the analysis, as many studies have reported it to have an important role in anti-inflammatory responses [ 20 ].…”
Section: Methodsmentioning
confidence: 99%
“…The profiling results and the outline of the study are briefly presented in the Additional file 1 . From the miRNAs whose expression significantly differed in asthmatics and controls in the profiling study, we chose those that had been previously tested in serum and were related to the presence of asthma or its clinical features [ 15 , 20 ]. Additionally, although not shown as significant in the profiling results, miRNA-126a-5p was also included in the analysis, as many studies have reported it to have an important role in anti-inflammatory responses [ 20 ].…”
Section: Methodsmentioning
confidence: 99%
“…Alhamwe et al [92] reviewed the role of histone modifications in different allergic conditions including asthma. Additionally, Svitich et al [92] and Weidner et al [93] reviewed the role of miRNAs in asthma and allergy. Recently, Wasti, Liu, and Xiang reviewed the role of different epigenetic classes including histone modifications and miRNA in asthma [94].…”
Section: Epigenomics Of Asthmamentioning
confidence: 99%
“…In asthmatic patients, the expression of let-7a, and miR-21, -133a, -155, -328 and -1248 in exhaled breath condensates has been shown to be significantly lower than in healthy individuals ( 64 ). Serum miRNA expression is age-dependent and is associated with clinical asthma features and systemic inflammation, suggesting that miRNAs play differential roles in the pathogenesis of asthma in patients from different age groups ( 65 ).…”
Section: Role Of Micrornas In the Pathogenesis Of Pulmonary Fibrosismentioning
confidence: 99%